TRAINING ON MAKING ECO-PRINT MOTIFS FOR COMMUNITY EMPOWERMENT IN BLITAR REGENCY - Listia Natadjaja; Heru Dwi Waluyanto; Ani Wijayanti (Fakultas Seni Rupa dan Desain ITB, 2021)
We see an opportunity to cultivate natural potentials in the Blitar Regency to be used as a means of improving then community’s welfare. One of the possible uses of the natural materials is the manufacture of eco-print products. The purpose of this research is to implement eco-print technique in producing eco-print products that will benefit in improving the welfare of the community. This community empowerment project involves 68 students that are divided into seven groups and are prepared in a Service-Learning method. There are some stages that the students go through in implementing this program outside the classroom, namely: learning the eco-print technique, practicing, providing training for the community, and innovating stages. Through this method of learning, students learn how to educate themselves and the community. The results of these trainings are eco-print motifs produced from the collaboration between students and the district community, eco-print motifs produced by the community, and the students’ innovative products.